Effects of Acupuncture and Rehabilitation Training on Limb Movement and Living Ability of Patients with Hemiplegia after Stroke - Juhua Zhang; Yingmei Mu; Yunxia Zhang (Behavioural Neurology)
Stroke is a disease with a high disability rate, having a serious impact on that patient’s working and daily survival quality and bringing economic burden to the family and society. Patients with stroke hemiplegia are mostly tetraplegic and have difficulty regulating their balance, and their long-term symmetry has been destroyed. The application in the rehabilitation process of acupuncture in patients with hemorrhagic stroke may produce unexpected effects. It is very effective to study the effect of acupuncture combined with rehabilitation training on limb movement and patient survival. It is very helpful in improving normal motor function and normal life, increasing joint mobility and muscle strength, and reducing muscle tension. In this paper, it is found that the observational group has a complication rate of 2.13%, in contrast to 17.02% as in the group of control, and the pin-prick combined with a rehabilitative training makes a significant improvement to the patients. This study provides suggestions for the study to investigate acupuncture combined with recovery exercise on limb movement and living capacities of people with stroke paraparesis.